Does Islamic interbank rate influence bank characteristics and economic cycle in Malaysian monetary transmission? - Muhammad, F.; Sulaiman, A.A.; Hussien, M.Y.M.; Razak, A.A. (Macrothink Institute, 2012)
This study aims to determine the effectiveness of Islamic Interbank Rate as the intermediary target by monetary policymakers in achieving economic goals. Via Islamic banking institutions as the mediator to channel the policy effect, the relevancy of this tool is identifiable. To attain this objective, a credit channel model was used by adapting macroeconomic variables and also bank specific variables. Data from 1997 until 2010 was regressed by using the Panel Data method with the application of interaction approach. The analysis finding shows that the IIR is capable in influencing the bank specific variables. Accordingly, Islamic banks are the significant intermediaries in ensuring the effect of policy implementation provides stimulation to the achievement of the desired economic goals. Besides, the significant pro cyclical nature through the interaction with the GDP, indicatesthe effect of this policy tool in influencing bank behavior to offer financing for the economic sectors parallel to the current economy.